Alternativas de etnodesenvolvimento na comunidade Chácara das Rosas em Canoas/RS: um estudo de memória social. - Nascimento, Jorge Luiz da Silva (2018)
Chácara das Rosas (Farm of Roses), a community located in the city of Canoas, State of Rio Grande do Sul, is one of the first quilombo’s remaining titled communities inserted in the Brazilian public policies (NASCIMENTO; GRAEFF, 2016). Due to the political participation of its leaders, it has acted as the protagonist of the breaking off with experiences of segregation and social invisibility. In this paper, we present a trial video about the community aiming also the qualification of its social demands as the expansion of its ethnodevelopment alternatives (STAVENHAGEM, 1984). The video is the partial result of an academic research under development since March 2017 entitled "Alternativas de etnodesenvolvimento na comunidade Chácara das Rosas em Canoas/RS: um estudo de memória social" (Ethno-development alternatives in Farm of Roses community, Canoas-RS: a study of social memory). As the title indicates, the purpose of the research is to identify ethno-development alternatives as to the remaining quilombo community Chácara das Rosas. More specifically, the search addresses to: 1) understand the genesis of Chácara das Rosas and its transformation process into a quilombo remaining community from the standpoint of its inhabitants; 2) map and describe the ethno-developmental activities employed by the community; 3) analyze the ethno-developmental activities of Chácara das Rosas, assessing the feasibility of their use by other quilombo’s remaining communities whether in the state of Rio Grande do Sul or in Brazil; and 4) create an extension course on ethno-development alternatives, organized by the researcher in partnership with the community leaders, with the aim to qualify other quilombo communities in the state of Rio Grande do Sul and throughout Brazil. The trial video mentioned here depicts the progress of the specific goals listed above over the months of May, June and July 2017. The partial results indicate that the community is becoming empowered by discussions on ethno-development, which strengthens the motive not only to create the extension course provided by the research project but also to adopt seminars and occasional actions addressed to the quilombo awareness as for its historical, social and memory importance.